2004
DOI: 10.1073/pnas.0406055102
|View full text |Cite
|
Sign up to set email alerts
|

An unusual signal peptide facilitates late steps in the biogenesis of a bacterial autotransporter

Abstract: Escherichia coli ͉ microbial pathogenesis ͉ protein folding ͉ protein translocation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
159
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(171 citation statements)
references
References 29 publications
7
159
5
Order By: Relevance
“…In this model, the expanded b-domain of Hbp would translocate the passenger domain while surrounded by the BamA oligomer. An expanded b-domain could be compatible with the observed translocation of small folded elements (Jong et al, 2007;Skillman et al, 2005). When translocation of the passenger is completed the Bam complex would disassemble, which might trigger the sealing of the bdomain and its folding into a stable barrel permitting the cleavage of the passenger domain.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…In this model, the expanded b-domain of Hbp would translocate the passenger domain while surrounded by the BamA oligomer. An expanded b-domain could be compatible with the observed translocation of small folded elements (Jong et al, 2007;Skillman et al, 2005). When translocation of the passenger is completed the Bam complex would disassemble, which might trigger the sealing of the bdomain and its folding into a stable barrel permitting the cleavage of the passenger domain.…”
Section: Discussionmentioning
confidence: 81%
“…Essentially, crystal structures of the b-domains of two ATs revealed a narrow 12-strand b-barrel pore structure with an inner diameter of 1.2 nm Oomen et al, 2004) that is incompatible with the reported secretion of small folded elements and closely spaced cysteine bridges engineered or naturally occurring in AT passenger domains Bodelon et al, 2009;Brandon & Goldberg, 2001;Jong et al, 2007;Oomen et al, 2004;Skillman et al, 2005). These incongruent data have led to discussions about the possible involvement of host factors in the OM translocation of ATs (Bernstein, 2007;Oomen et al, 2004).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations